Hipercontratilidade das artérias mesentéricas de resistência em ratos infectados com Strongyloides venezuelensis - Schönholzer, Tatiane (2017)
Strongyloidiasis can cause structural damage to the mesenteric vasculature due to the migration of L3 larvae to this region, which serves as a gateway for these parasites to transit systemically. However, little is known about the involvement of vascular function in relation to this parasitemia. The objective of this work was to evaluate the contraction and vascular relaxation response in the resistance mesenteric arteries of rats inoculated experimentally with Strongyloides venezuelensis L3 larvae. Male Wistar rats aged 12-14 weeks were inoculated intraperitoneally with 2,000 Strongyloides venezuelensis L3 larvae, while the control group received saline solution via the same route. Extraction of the 2nd and 3rd order mesenteric arteries of the animals were performed after death, with 10 days in the control and 10 DPI (days postinoculation) and 30 days in the 30 DPI group. In the 10 DPI and 30 DPI groups, the eggs in the feces of the animals were counted, where the parasitic load in the 10 DPI group, with 28,246 ± 6 eggs per gram of feces (EPG), were significantly increased (p<0.05) compared to the 30 DPI group with 1,883 ± 0.7 EPG. The values for the adult intestinal worms count after dissection in the 10 DPI group were 273 ± 37.4, it was significantly higher (p<0.01) than the 30 DPI group with 119 ± 33. Through the concentration-response to phenylephrine was shown to have increased contractile response to phenylephrine in the 30 DPI group, relative to the control or to the 10 DPI group. With inhibition of nitric oxide synthase with L-NAME (100 μM, 40 minutes), the difference in the contractile response between the 30 DPI and 10 DPI groups was abolished, but not between the 30 DPI group and the control, demonstrating a possible increase in the production of nitric oxide in the 10 DPI group. By inhibiting cyclooxygenase with indomethacin (10 μM, 40 minutes), the differences in the contraction response between the 30 DPI group and the other experimental groups were extinguished, evidencing that both thromboxane A2 and prostaglandins may be elevated after 30 DPI. Endothelium-dependent relaxation assessed with acetylcholine was similar across all groups, with no apparent involvement of vasodilation during this disease. It is concluded that the increase in contraction in the arteries of the 30 DPI group was observed even after the reduction of the parasite load, which may be due to the production of contractile factors derived from the endothelium, the presence of the worms or their by-products and/or to the immune system of the animals, resulting in persistent endothelial dysfunction after 30 DPI.